Soundwalking with AI: collaborative creativity as embodied learning - Galvão, Martim S.; Sagesser, Marcel Zaes (Frontiers in Computer Science, 2025)
This paper presents an innovative approach to designing soundwalks in educational group settings by harnessing AI, particularly ChatGPT, to inspire collaborative auditory imagination and soundscape creation. By serving as an interlocutor during a group script formulation process, ChatGPT aids in transforming student recollections of a city's sound marks into a textual description of the group's collective auditory imagination. This imagination is refined through a social, collaborative prompt engineering exercise into a concise soundwalk script. Over the course of a week, students then individually bring the co-created script to life, through an embodied practice that includes capturing the required sounds in the field and assembling them in digital audio workstations, before presenting their interpretations to the class. Conducted at California State University, San Bernardino, in Spring 2023 with a group of four students, this pedagogical experiment showcases an adaptable method for teaching collaborative creativity at the intersection of human perception and emerging technologies such as AI. Highlighting the interplay between auditory experiences, collective vs. individual imagination, and language, the research underscores AI's dual role as facilitator and collaborator, supporting varied creative expressions beyond a singular AI-generated narrative. Participants recognized AI's usefulness for streamlining the collaborative process of crafting a script but noted its limitations in emotional depth, sparking a discussion on the necessity of human involvement in refining AI content. Within this paper, the authors suggest an AI-assisted pedagogical model designed to facilitate student participation in both collective and individual modes of learning and creativity. They critically assess both the advantages, limitations, and ethics of their pedagogical experiment in the creative arts and contribute to the larger discourse of human-AI collaboration within creative media education. In spite of the small sample size of the experiment, the account offers a reflexive practice in rethinking how technology has the potential to innovate learning. This research effectively advances social innovation by integrating emerging technologies, especially artificial intelligence, into group learning settings in digital media creation.